Evaluation of the Application of Blended Learning in Arabic Learning at Sidoarjo Junior High School - Lailatul Farikhah; Farikh Marzuki Ammar (Universitas Muhammadiyah Sidoarjo, 2023)
Blended learning is a mixture of traditional education as well as an area of ​​electronic education. Blended Learning is defined as Blended from the initial word